Historical Anatomy On Issues of Language Decay, Survival and Change - Iyanda Kamoru (Emerging Trends in Languages, 2024)
This paper examines issues of language decay, survival and change. The fortunes of language can rise and fall and are intimately linked to the fortunes of their speakers. In the modern world, relatively few languages are becoming more widely spoken, and smaller languages are finding it harder and harder to survive. Prospects are not totally dire, though; several smaller languages have been successfully resurrected, and efforts are in motion to do the same for additional languages. Change is one of the unique characteristics of human language.. As long as language is in constant use by human beings, it is subjected to unimaginable change. Any language that no longer changes commits natural linguistic death. This is the fate suffered by classical Hebrew as well as Manx language. These changes occurred initially without the notice of the users but as goes on they become noticeable by the speech community. The survival, change, and death of languages are intricate processes that are closely linked to the destiny of their speakers. A few languages are seeing an increase in speakers in the globalized world of today, whereas lesser languages are finding it difficult to survive. Nevertheless, despite the difficulties, there are reasons for optimism, as attempts to bring endangered languages back to life have showed promise. One of the things that makes language so unique is its fluidity.
Keywords: Language; Language Decay; Survival Community and Linguistic